Advertising vs. R&D: Relative effectiveness on brand equity - J. Jeong (South African Journal of Business Management, 2015)
This study examines whether advertising can contribute directly to brand equity and, if it can, determines how much value advertising can deliver to brands and firms using the secondary data from various sources. The findings show that advertising can not only work to improve market performance measures but also to develop and maintain brand equity. R D is also found to positively affect brand equity. With regard to the relative effectiveness of advertising and R D, R D is more effective than advertising in contributing to brand equity when measuring absolute effects of expenditures. When measuring simple changes in brand equity, however, changes in advertising are more effective than changes in R D.
Keywords: 650